The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2196/18371
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Emotions, Social Media Use, and Sun Exposure Among Young Women: Ecological Momentary Assessment Study

Abstract: Background Research has pointed to a connection between social media use, emotions, and tanning behaviors. However, less is known about the role specific emotions may play in influencing social media use and how emotions and social media use may each be associated with outdoor tanning. Objective This paper aims to examine the connection between emotions, social media use, and outdoor tanning behaviors among young women, a group particularly important fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…There is additionally a dearth of research on how individuals’ use of SM prospectively predicts their emotion. The few studies that exist have yielded inconsistent findings, with some finding associations between SMU and momentary positive emotion (Lin & Utz, 2015) and others with momentary negative emotion (e.g., Willoughby et al, 2020). We propose that these mixed findings may be explained, at least in part, by the ways in which individuals use SM.…”
Section: Discussionmentioning
confidence: 99%
“…There is additionally a dearth of research on how individuals’ use of SM prospectively predicts their emotion. The few studies that exist have yielded inconsistent findings, with some finding associations between SMU and momentary positive emotion (Lin & Utz, 2015) and others with momentary negative emotion (e.g., Willoughby et al, 2020). We propose that these mixed findings may be explained, at least in part, by the ways in which individuals use SM.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies have assessed the influence of SMU on momentary emotion, and they have also yielded inconsistent findings. For instance, laboratory-based studies have found that using SM, compared to using other websites, predicts low levels of positive affect (PA) and high levels of NA (Fardouly et al, 2015; Yuen et al, 2019), and SMU predicts increases in momentary NA (Berry et al, 2018; Willoughby et al, 2020), suggesting SMU has contrahedonic impacts on momentary emotion. However, in an experience sampling study, SMU engagement was contemporaneously associated with diminished levels of NA (Yin et al, 2022), suggesting SMU has hedonic impacts on momentary emotion in everyday life contexts.…”
mentioning
confidence: 99%